Influence Service Prime to Satisfaction Student in Universitas Terbuka (Ut) Ternate - Agung Bayumurti Wijaya; Eha Saleha; Andi Wijaya (Britain International for Academic Research (BIAR) Publisher, 2025)
Many educators believe that correspondence learning or distance learning is merely a business venture. As a result, institutions offering correspondence or distance learning are often viewed negatively and their quality is questioned. However, the need to provide equal access to educational opportunities has always been a part of democratic ideals. Distance learning has brought about innovations such as the use of audio teleconferencing and computers, which have influenced the delivery of education in public schools, higher education, the military, business, and industry, and have encouraged the use of the internet, particularly in higher distance education. Universitas Terbuka is one of the higher education providers based on distance learning. As an educational service provider, delivering excellent service impacts student satisfaction. Excellent service must be measured regularly to assess student satisfaction, especially at Ternate Universitas Terbuka , where there is a high urgency due to the growing need to strengthen educational capacity as student enrollment increases. This study uses a quantitative approach with data analysis conducted through multiple regression. The population of this study consists of undergraduate students at Ternate Universitas Terbuka during the 2024.1 registration period, totaling 1,975 students. Using Slovin's formula, a sample of 100 undergraduate students from Ternate Universitas Terbuka was selected. The results of the study indicate that physical evidence, reliability, assurance, and responsiveness do not have a positive and significant effect on student satisfaction at Universitas Terbuka when considered individually. However, technology and empathy do have an influence on excellent service at Ternate Universitas Terbuka , thereby affecting student satisfaction.